Batik wastewater treatment using membrane bioreactor (MBR) - Saidah Malihah, Mansor (2010)
Batik industry is one of our country's economy sources. However, this industry waste contributes to water pollution as the final stages of batik making discharges contaminated water which contains wax, dye, grease and others. The current treatment of the wastewater which is applied by this industry is activated sludge plant which needs stages of treatment. The aims of this research are to determine the characteristics of untreated and treated batik wastewater and to determine the effects of hydraulic retention time (HRT) to the batik wastewater .A laboratory-scale MBR was set up and fed up with batik wastewater with addition of municipal sludge from Taman Mahkota Aman treatment plant in order to assist the biodegradation of the batik wastewater. The MBR was operated at aeration intensity of 31iters/ minutes under room temperature. The pressure for 24 hours, 48 hours, 72 hours and 96 hours of the hydraulic retention times (HRT were manipulated. At 24 hours of HRT, the flux was the highest with 19.290 x 10 m/s at 399.9761 milibar. The flux increased as the applied pressure increased and as the HRT increased, the flux value decreased. The suspended solid at 96 hours of HRT was 35 mg/l and decrease over FIRT due to blocked pores of the membrane filter. While the MLSS in reactor increased over HRT as sludge yield in the reactor. Although the MBR has problem with fouling, the reliable data collected from the experiment could be used to improve the effectiveness of treating batik wastewater.